Pengaruh Konvensasi Terhadap Motivasi Kerja Pegawai di Kantor Kecamatan Kulo Kabupaten Sidenreng Rappang - Andi Astinah Adnan (JIA: Jurnal Ilmiah Administrasi, 2012)
Abstract The research has been done place at Kulo District Office in Sidrap regency for about 2 months from August to September in 2011. The research's goal is to determine how compensation affects employee's work motivation at Kulo District Office, and all the influencing factors. The methods used to collect data are: field observation, questionaire, interview, and literature study. The those data was analyzed using frequency and percentage table. The research's population took forty (40) people, all accounted as research's sample. The result shows that 77,50% of sample agreed that compensation affect employee's motivation. 62,50% of all employees also agreed that they were more motivated to work after receiving compensation. The compensation did help employee's life and healthiness, approved by 85% of sample. Attending intensitivity also increased to 72,50% of workers. And 55% of them showed a good profesionalism to serve residential people around Kulo District Office. Still there are quite a few of unconstructive factor in serving residential people at Kulo District Office: unsatisfactory office's facility approved by 57,50% of serving employee; and unsufficient non-employee education level by 55%. While the constructive factors are the compensation given to non-employee by 70% of respondent, also discipliness and cooperation among employees by 77,50%.